God accepts a broken spirit and a contrite heart - Thoughts on penitence, forgiveness and reconciliation in Psalm 51 - Human, Dirk J. (Verbum et ecclesia, 2005)
A concern with reconciliation amidst broken relationships permeates the religious discourse of human spirituality. In addition, in the history of Christian spirituality in particular, the role of penitence has been considered to be an integral part of authentic faith in a fallen world blighted by sin. With this as background, the present article discusses the biblical text of Psalm 51, a poignant and dramatic rendering of a sinner’s penitence in his quest for forgiveness and reconciliation. Acutely aware of his transgressions, the psalmist confesses his own sinfulness whilst acknowledging the divine requirement of genuine repentance and complete dependence on God’s grace. With these thoughts, Psalm 51 also allows the reader to discover for him/ herself the process of repentance - penitence - forgiveness - renewal and, ultimately, reconciliation.